Oenothein B ameliorates hepatic injury in alcoholic liver disease mice by improving oxidative stress and inflammation and modulating the gut microbiota - Xu, Lu; Li, Wei; Chen, Shu-yi; Deng, Xi-wen; Deng, Wei-feng; Liu, Guo; Chen, Yun-jiao; Cao, Yong (Frontiers in Nutrition, 2022)
Alcoholic liver disease (ALD) is a global health problem, however there are few effective treatments. Oenothein B (OEB) is a macrocyclic dimer ellagic tannin that possesses abundant biological activities including antioxidant, anti-inflammation, antitumor, immunomodulatory, and antimicrobial properties. In this study, the hepatoprotective effect of OEB against ALD was investigated in vivo and in vitro. We found that OEB treatment dramatically reduced alcohol-induced hepatic injury, as evidenced by decreased levels of aminotransferases and inflammatory biomarkers and increased antioxidant capacity in OEB-treated groups. OEB treatment alleviated oxidative stress by upregulating the Keap1/Nrf2 signaling pathway and inhibited inflammation by downregulating the TLR4/NF-κB signaling pathway. Additionally, OEB treatment positively improved alcohol-induced intestinal microbial dysbiosis by modulating the structure and composition of gut microbiota. Interestingly, we observed increased short-chain fatty acid (SCFA) producers (Muribaculaceae) and decreased Gram-negative bacteria (Akkermansia) in the OEB treatment groups, which may contribute to the inhibition of hepatic oxidative stress and inflammation via the gut-liver axis. In summary, our findings indicate that OEB is a promising therapeutic strategy for preventing and treating ALD.